Syngenta Enogen Corn Fed as Corn Grain and Corn Silage in Diets Containing Corn Coproducts Did Not Enhance Diet Digestibility in Growing Heifers - M. A. Scilacci; M. A. Johnson; E. C. Titgemeyer; S. P. Montgomery; A. J. Tarpoff; E. D. Watson; W. R. Hollenbeck; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:Evaluate the effect of feeding corn grain and corn silage from Enogen corn (EC; Syngenta Seeds, LLC., Downers Grove, IL) or conventional corn (CON) in diets containing either wet distillers grain (WDG; ICM Biofuels, St. Joseph, MO) or Sweet Bran [proprietary wet corn gluten feed (WCGF); Cargill Animal Nutrition, Blair, NE] on intake and digestibility in growing cattle. Study Description:Eight ruminally cannulated crossbred heifers (initial body weight = 816 ± 94 lb) were used in an intake and digestibility study designed as a replicated 4 × 4 Latin square. Four consecutive, 15-day periods consisted of 10 days for diet adaptation, 4 days of fecal sampling, and 1 day of ruminal sampling. Heifers were fed once daily at 10:00 a.m. Chromic oxide (Cr2O3) was used as an external digestion marker to calculate apparent total-tract diet digestibility. Results:Heifers eating EC tended to have greater starch digestibility (P= 0.07) than heifers eating CON. No differences (P>0.34) in dry matter or fiber digestibilities were observed between corn sources. There were coproduct × hour interactions for concentration of ruminal ammonia (P<0.01) and two branched chain fatty acids, isobutyrate (P<0.01) and isovalerate (P<0.01). In heifers fed WCGF, isobutyrate and isovalerate concentrations reached a peak at 2 hours after feeding, then declined between 2 and 24 hours after feeding. Heifers fed WDG isobutyrate and isovalerate concentrations were greatest at 0 hours after feeding. Differences between concentrations of isobutyrate and isovalerate can be explained by differences in protein digestibility of WCGF and WDG. The Bottom Line:Enogen corn hybrids fed as dry rolled corn and corn silage in diets containing corn coproducts did not result in better diet digestibility compared to conventional corn hybrids, but diets containing WDG may offer better growth performance (Scilacci et al., 2022) for growing cattle due to more ruminally undegradable protein compared to diets containing WCGF.
Keywords: Enogen corn hybrids; corn coproducts; diet digestibility